COMPARATIVE ANALYSIS OF PHRASEOLOGICAL UNITS WITH THE COMPONENT OF PRECIOUS STONES AND METALS IN ENGLISH AND RUSSIAN LANGUAGES WITHIN THE PHRASEOSEMANTIC FIELD OF "KINDNESS" (Scientific journal of the Fergana State University, 2025)
The article analyzes phraseological units in the English and Russian languages with the component of precious stones and metals within the semantic field of "Kindness." The semantic analysis and classification of phraseological units with components of precious stones and metals emphasize their role in the linguistic worldview. The methods of comprehensive sampling, component analysis, and a cognitive-linguistic approach were applied to identify the national and cultural specifics of perceiving precious stones and metals. The results reveal that the studied cultures' phraseological units associated with gold and precious stones symbolize kindness, nobility, generosity, and sincerity. English phraseological units highlight qualities such as moral resilience and eloquence, while Russian phraseological units emphasize diligence, responsiveness, and kind-heartedness. The study demonstrates the universality of the symbolism of precious metals and stones as markers of high human qualities and their cultural peculiarity, contributing to a deeper understanding of the values of different cultures.